RETRACTED ARTICLE: Downregulated long non-coding RNA SNHG7 restricts proliferation and boosts apoptosis of nasopharyngeal carcinoma cells by elevating microRNA-140-5p to suppress GLI3 expression. Issue 4 (16th February 2020) - Dai, Yaozhang; Zhang, Xin; Xing, Haijie; Zhang, Yamin; Cao, Hua; Sang, Jianzhong; Gao, Ling; Wang, Liuzhong
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Yaozhang Dai, Xin Zhang, Haijie Xing, Yamin Zhang, Hua Cao, Jianzhong Sang, Ling Gao, and Liuzhong Wang. Downregulated long non-coding RNA SNHG7 restricts proliferation and boosts apoptosis of nasopharyngeal carcinoma cells by elevating microRNA-140-5p to suppress GLI3 expression. Cell Cycle. 2020;19(4):448-463. doi: 10.1080/15384101.2020.1712033. Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to address all the concerns raised and have not been able to provide all their original data or sufficient supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted.'